Polymeric Materials for Wastewater Treatment Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
In view of the relevant contributions that polymers and polymeric materials may make in the conservation of the aquatic environment—namely, through their use in wastewater treatment—a Special Issue (SI) entitled “Polymeric Materials for Wastewater Treatment Applications” aimed to publish original research and review papers within this field. Scientific contributions related to any aspect of the utilization of polymers and polymeric materials—whether synthetic or natural—in the treatment or purification of wastewater were welcomed. Given the large spectrum of materials, types of pollution, and treatment processes, this was a widely inclusive SI, which succeeded in gathering very relevant scientific contributions. Dr. Marta Otero and Dr. Ricardo N. Coimbra, as Guest Editors of this SI, acknowledge all contributors and peer-reviewers that allowed for such a success and are happy to share a compilation of the published papers in this book.